Accuracy of point of care ultrasound in the diagnosis of long bone fractures in the emergency department - Joshi, Dipesh Mangal; Maharjan, Rony; House, Darlene Rose; Shrestha, Smriti (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Long bone fractures account for a significant portion of injuries in the emergency department (ED). This study aimed to determine the accuracy of point of care ultrasound (POCUS) compared to x-ray in the diagnosis of long bone fractures in the ED. Method: This cross-sectional study assessed 147 patients presenting to the ED of Patan Academy of Health Sciences (PAHS), with suspected long bone fractures, from Oct 2021 through Jun 2022. In all patients, POCUS examination was done by emergency fellows and then standard plain x-ray was performed. Data were analyzed by SPSS 28.0 to determine sensitivity and specificity. Result: A total of 147 patients were included in the study. Compared with x-ray, sensitivity, specificity, PPV and NPV of POCUS in determining fractures was found to be 86%, 98.96%, 97.72% and 93.2%, respectively. Based on bone injured, the highest sensitivity and specificity were obtained with forearm fractures, which was equal to 97.22% and 100%, respectively. Based on age categorization, the highest sensitivity (100%) and specificity (100%) were obtained in pediatric age group i.e. up to 16 years. Conclusion: This study demonstrated that POCUS has high sensitivity and specificity in the diagnosis of long bone fractures, compared to x-ray.